Robotic total knee arthroplasty with a cruciate‐retaining implant: a 10‐year follow‐up study - Yang, Hong Yeol; Seon, Jong Keun; Shin, Young Joo; Lim, Hong An; Song, Eun Kyoo (Clinics in orthopedic surgery, 2017)
This study compared clinical and radiological results between robotic total knee arthroplasty (TKA) and conventional TKA with a cruciate-retaining implant at 10-year follow-up. The hypothesis was that robotic TKA would allow for more accurate leg alignment and component placement, and thus enhance clinical and radiological results and long-term survival rates. A total of 113 primary TKAs performed using a cruciate-retaining implant in 102 patients from 2004 to 2007 were reviewed retrospectively. Of the 113 TKAs, 71 were robotic TKAs and 42 were conventional TKAs. Clinical outcomes (visual analogue scale pain score, Hospital for Special Surgery score, Western Ontario and McMaster University score, range of motion, and complications), radiological outcomes, and long-term survival rates were evaluated at a mean follow-up of 10 years. Clinical outcomes and long-term survival rates were similar between the two groups. Regarding the radiological outcomes, the robotic TKA group had significantly fewer postoperative leg alignment outliers (femoral coronal inclination, tibial coronal inclination, femoral sagittal inclination, tibial sagittal inclination, and mechanical axis) and fewer radiolucent lines than the conventional TKA group. Both robotic and conventional TKAs resulted in good clinical outcomes and postoperative leg alignments. Robotic TKA appeared to reduce the incidence of leg alignment outliers and radiolucent lines compared to conventional TKA.